Fotografar a dança como uma prática poética - Silva, Natália Oliveira Cunha da (2015)
In this research, based on my everyday practice as a photographer technician of the Dance BA at the Federal University of Uberlândia (UFU) registering events, as well as students and teachers‟ works, I analyze what are the possibilities of documenting dance through photography and how they articulate in the context which I am inserted. I had done some exercises/theoretical reflections, aiming to point out a few experiences of this practice, that have helped me consolidate both making and thinking about photographing dance in interaction whit its environment; and have also given me the possibility to think that images have their own emancipation from themselves, expanding their meanings, offering new ways of observation and refreshing the memory